PENGARUH KOMPETENSI, BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN PADA EFEKTIVITAS SISTEM PENGENDALIAN INTERN PENGADAAN BARANG/JASA PEMERINTAH - Kibtiyah, Muhimatul; Wirakusuma, Made Gede; Ratna Sari, Maria M. (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
Th e study aimed to get empirical evidence about the influence of competence, organizational culture and leadership style s on the effectiveness of internal control systems of the Government Goods/Services Procurements in the Ministry of Religion of Bali. The entire work unit s in the Ministry of Religion were taken as the study population. The s ampling technique us ed purposive sample . The n umber of samples was 43 procurement officials. The analysis used was the multiple linear regression. The research proves that: (1) Competence positive ly influence d on the effectiveness of internal control systems  of government goods/services procurement ; (2) O rganization al culture positively influenced on the effectiveness of the internal control system of procurement of government goods/services; and (3) style of leadership positive ly influence d on the effectiveness of internal control systems of procurement of government goods/services .
Keywords: organizational culture, leadership style, competence,effectiveness of the ICS